2008
DOI: 10.3181/0706-rm-169
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Intestinal Mucosal Apoptosis by Ghrelin in Fasting Rats

Abstract: Ghrelin is mainly produced in the stomach and has several physiologic functions. The aim of this study was to investigate whether ghrelin regulates apoptosis in the small intestinal mucosa of fasting rats. Intestinal mucosal apoptosis was evaluated as the percentage of fragmented DNA, villus height, and terminal deoxynucleotidyl transferase-mediated dUDP-biotin nick end-labeling (TUNEL) staining and by Western blot analysis of caspase-3 in 48-hr fasting rats. Crypt cell proliferation was evaluated by counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 51 publications
3
13
0
2
Order By: Relevance
“…This is the very first study reporting that ghrelin treatment decreases the number apoptotic cells, PAR and caspase-3 expressions while increasing Ki67 expression in gastric mucosa exposed to Na 2 S 2 O 5 . Similar to our findings Park et al have demonstrat ed that ghrelin enhances the proliferation of crypt cells in the small intestine and attenuates intestinal apoptosis (Park et al, 2008 ). Moreover, several reports suggested that ghrelin decreases TUNEL positive rate and caspase 3 levels in endothelial cells, spinal cord and neurons (Lopez et al, 2012;Zhang et al, 2012;Zhao et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
“…This is the very first study reporting that ghrelin treatment decreases the number apoptotic cells, PAR and caspase-3 expressions while increasing Ki67 expression in gastric mucosa exposed to Na 2 S 2 O 5 . Similar to our findings Park et al have demonstrat ed that ghrelin enhances the proliferation of crypt cells in the small intestine and attenuates intestinal apoptosis (Park et al, 2008 ). Moreover, several reports suggested that ghrelin decreases TUNEL positive rate and caspase 3 levels in endothelial cells, spinal cord and neurons (Lopez et al, 2012;Zhang et al, 2012;Zhao et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
“…The protective effect has also been demonstrated in experimental colitis [57]. A recent study showed that, both intraperitoneally and centrally administered, ghrelin suppresses mucosal intestinal apoptosis in fasting rats [113].…”
Section: Gastrointestinal Functionmentioning
confidence: 94%
“…Ghrelin protected hypothalamic neurons from oxygen glucose deprivation insult by inhibiting reactive oxygen species generation and stabilizing mitochondrial transmembrane potential [160]. The anti-apoptotic effect of ghrelin has been reported in several other cells such as pancreatic b-cells [156], intestinal epithelial cells [161], adipocytes [162], cardiomyocytes and endothelial cells [163]. The anti-apoptotic effect of ghrelin seems to be mediated via phosphatidyl inositol 3-kinase (PI3K) activation and glycogen synthase kinase-3b (GSK-3b) suppression, and stabilization of b catenin [164].…”
Section: Anti-apoptotic Effectmentioning
confidence: 97%